2000
DOI: 10.1063/1.372380
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic model for metalorganic chemical vapor deposition from trimethylgallium and arsine

Abstract: A kinetic model based on the collision theory of chemical reactions is proposed for gallium arsenide (GaAs) metalorganic chemical vapor deposition from trimethylgallium and arsine. A simplified reaction mechanism is incorporated into the model, which includes four heterogeneous deposition reactions: Ga-containing and As-containing species with Ga and As sites, as well as carbon incorporation reactions. An equation for the overall growth rate of the four deposition reactions is derived, which is simplified unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…At this temperature region, the activation energy is estimated to be as low as 5 kcal mol −1 (0.22 eV), indicating the near mass transport limited region. 27 With a further increase of growth temperature, the growth rate decreases, which is mainly attributed to the surface desorption or the gas phase reaction. 28 The VI/III ratio dependent growth rate is also shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At this temperature region, the activation energy is estimated to be as low as 5 kcal mol −1 (0.22 eV), indicating the near mass transport limited region. 27 With a further increase of growth temperature, the growth rate decreases, which is mainly attributed to the surface desorption or the gas phase reaction. 28 The VI/III ratio dependent growth rate is also shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease of k s also suggests the surface reaction of As-atoms with As-sites. There are four elementary heterogeneous reactions on GaAs surface [15]: Ga-species reaction on Ga-sites; Ga-species on As-sites; As-species reaction on Ga-sites; and As-species on As-sites, among which the deposition of As-species on As-sites is a selflimited process with a small sticking coefficient or high E a . However, it is also reported that reactions between group V species and group V sites do occur.…”
Section: Dependency Of K S On P Tbasmentioning
confidence: 99%
“…Lines are guides to the eye. Experimental data from [199] Deviation from the ideal stoichiometry introduces point defects that can be electrically active and change conductivity type and carrier concentration. In the case of CuInSe 2 , excess Cu could go on interstitial positions or promote selenium vacancies, both leading to n-type behavior.…”
Section: Amphoteric Impuritiesmentioning
confidence: 99%